ANALISIS KEPUASAN PELANGGAN MIGRASI PRABAYAR DI WILAYAH PT PLN (Persero) RAYON KROYA - Irmawati Irmawati; R. Sahedhy Noor SK (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
The research aimed to examine customer satisfaction of prepaid electricity PLN Rayon Kroya using model that developed by Parasuramanet.al.consist of variables tangibles, reliability, responsiveness, assurance, andemphaty. One hundred respondents were chosen as samples by purposive sampling method. Data were analyzed by Compare Mean: Paired Sample T-Test. The result showed that there were not significant differences between customer expectation and customer perceived services on prepaid electricity PLN Rayon Kroya consist of variables tangible, reliability, responsiveness, assurance and empathy. It is concluded that PLN Rayon Kroya able to achieve the quality of their services which could satisfy the customers expectations. It was because the management PLN Rayon Kroya could interpret the services quality expected by the customers. Keywords : tangibles, reliability, responsiveness, assurance, emphaty, services, and satisfaction